2017
DOI: 10.1111/1471-0528.15003
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Cervical mucus removal prior to intrauterine insemination: a randomized trial

Abstract: Objective To detect if removing the cervical mucus before performing intrauterine insemination (IUI) could improve pregnancy outcomes in patients with unexplained infertility.Design Prospective randomized study.Setting An Egyptian University Hospital.Population Seven hundred and fourteen couples with unexplained infertility who underwent intrauterine insemination (IUI) with or without cervical mucus removal.Methods Using computer-generated numbers, patients were randomly allocated to cervical-mucus-removal (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…have reported that after aspirating the cervical mucus before intrauterine insemination (IUI) in women with unexplained infertility, 13 the pregnancy rates increased over that in the non‐aspirated group (24% vs 9.5%, respectively) Maher et al . have demonstrated that among patients with unexplained infertility, 14 the pregnancy rate in the group with the cervical mucus removed was higher than that in those with the cervical mucus still intact (31% vs 21.8%, respectively). Simsek et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…have reported that after aspirating the cervical mucus before intrauterine insemination (IUI) in women with unexplained infertility, 13 the pregnancy rates increased over that in the non‐aspirated group (24% vs 9.5%, respectively) Maher et al . have demonstrated that among patients with unexplained infertility, 14 the pregnancy rate in the group with the cervical mucus removed was higher than that in those with the cervical mucus still intact (31% vs 21.8%, respectively). Simsek et al .…”
Section: Discussionmentioning
confidence: 96%
“…12 In patients with unexplained infertility, we found that SLPI levels in the cervical mucus were remarkably increased compared to those in the control group, and the results of several studies may support our findings. For example, Simsek et al have reported that after aspirating the cervical mucus before intrauterine insemination (IUI) in women with unexplained infertility, 13 the pregnancy rates increased over that in the non-aspirated group (24% vs 9.5%, respectively) Maher et al have demonstrated that among patients with unexplained infertility, 14 the pregnancy rate in the group with the cervical mucus removed was higher than that in those with the cervical mucus still intact (31% vs 21.8%, respectively). Simsek et al have speculated that even a small amount of cervical mucus injected into the endometrial cavity by an insemination catheter leads to low pregnancy rates by negatively affecting sperm motility and the sperm-oocyte interaction.…”
Section: Discussionmentioning
confidence: 99%
“…C ervical mucus is one of the factors which play a role in natural fertilization and also being the place for sperm capacitation (Maher et al, 2018). Cervical mucus is a biological environment that affects sperm survival and determines the ability of cows to become pregnant (Beran et al, 2013).…”
Section: Introductionmentioning
confidence: 99%